Managing persistent physical symptoms when being social and active is the norm: a qualitative study among young people in Denmark - Julie Høgsgaard Andersen; Mette Bech Risør; Lisbeth Frostholm; Mette Trøllund Rask; Marianne Rosendal; Charlotte Ulrikka Rask (BMC, 2023)
Abstract Background An increasing number of young people in Western countries report persistent physical symptoms (PPS). PPS may disturb everyday activities and they may have negative consequences for later adult mental and physical health. Still little is known about how young people handle PPS in their everyday lives. This study examines how young people with PPS attempt to manage their symptoms while staying engaged in their daily activities and what is at stake in these attempts. Methods This qualitative study involved semi-structured interviews with 11 young people with PPS. Photo-elicitation was used to capture the participants' experiences as they occurred in their everyday lives. The data material was analysed using a thematic analysis approach, as well as theory on subjectivity and social acceleration. Results The participants employed alleviating measures and tried to find patterns between their activities and the severity of their symptoms in order to adjust their activity level. Decisions not to participate in social activities were accompanied by feelings of missing out. The participants' attempts at adjusting their activity level was challenged by norms of being social and active, and they experienced difficulty prioritizing their activities and explaining their symptoms to others. Conclusion PPS shaped the participants' sense of how to act towards their bodies and social relationships in interaction with societal norms. The participants' subject formation and symptom experiences should thus be seen as a biosocial process.